2005
DOI: 10.1103/physrevlett.95.250601
|View full text |Cite
|
Sign up to set email alerts
|

Large-nExcitations in the Ferromagnetic Ising Field Theory in a Weak Magnetic Field: Mass Spectrum and Decay Widths

Abstract: In the presence of a small magnetic field h, the elementary excitations in the scaling two-dimensional Ising model are studied perturbatively in in the ferromagnetic phase. For excitations with large numbers n, the mass spectrum is obtained in the first order in h. The decay widths of excitations with energies above the stability threshold are calculated in the leading h3 order.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 15 publications
0
78
0
Order By: Relevance
“…The integrand involves the connected part 7 of the time-ordered product of the Heisenberg field operators. In principle, the matrix element in (3.8) can be handled through the intermediate-state decomposition, with the use of the form-factors 10) available in an explicit form [18]. Since the form-factors (3.10) vanish at θ 1 − θ 2 = 0, this expansion directly confirms the property (3.4).…”
Section: This Leads To the Representationmentioning
confidence: 87%
See 1 more Smart Citation
“…The integrand involves the connected part 7 of the time-ordered product of the Heisenberg field operators. In principle, the matrix element in (3.8) can be handled through the intermediate-state decomposition, with the use of the form-factors 10) available in an explicit form [18]. Since the form-factors (3.10) vanish at θ 1 − θ 2 = 0, this expansion directly confirms the property (3.4).…”
Section: This Leads To the Representationmentioning
confidence: 87%
“…When η changes, the spectrum of stable particles gradually changes from an infinite tower of "mesons" in the "low-T " regime at η → +∞ to a single particle in the"high-T " regime η → −∞. On a quantitative level, various expansions of some of the masses near the integrable points are available through the perturbation theory [3,[7][8][9][10][11][12][13], and rather accurate numerical data were obtained [7,8] by means of the "truncated conformal space approach" of [14], and by the numerical diagonalization of the lattice transfer-matrix [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This can proceed in a number of manners; we consider in particular the energies computed via a semiclassical approximation (the salient points of which are summarized in Appendix C). [95][96][97] One achieves consistent results by means of a Bethe-Salpeter analysis, which also allows one to obtain the wave function in Eq. (18), see also Appendix D. Computed results for the energies of meson states are also shown in Fig.…”
Section: The Nature Of the Rare Statesmentioning
confidence: 97%
“…Moreover, integrability at τ = 0 [25] also allows analytic investigation for strong magnetic field. Several studies, both analytic and numerical, have confirmed the McCoy-Wu scenario and provide us with a detailed description of the mass spectrum of Ising field theory in the full τ -h plane [3,25,10,26,24,27,28,29,30,31] (see also [32] for an introductory review of Ising field theory).…”
Section: Positive Magnetic Fieldmentioning
confidence: 99%